Does liquidity regulation impede the liquidity profile of collateral? - Kirsten Schmidt (European Central Bank (ECB), 2019)
We analyze the pledging behavior of Euro area banks during the introduction of the liquidity coverage ratio (LCR). The LCR considers only a subset of central bank eligible assets and thereby offers banks an arbitrage opportunity to improve their regulatory ratio by altering their collateral pledging with the European Central Bank. We use the existence of national liquidity requirements to proxy for banks' incentives to exploit this differential treatment of central bank eligible assets. Using security-level information on collateral pledged with the central bank, we find that banks without a preceding national liquidity requirement pledge more and less liquid collateral than banks with a preceding national liquidity requirement after the LCR introduction. We attribute the difference across banks to a preparation effect of the liquidity regulation on the national level.
Keywords: G21; G28; E42; E52; E58; 330; Liquidity regulation; monetary policy; central bank refinancing operations